Short-term brain atrophy evolution after initiation of immunotherapy in a real-world multiple sclerosis cohort: short communication - Nold, Ann-Kathrin; Wittayer, Matthias Sebastian; Weber, Claudia Ellen; Platten, Michael; Gass, Achim; Eisele, Philipp (Journal of neuroimaging, 2023)
Background and Purpose In multiple sclerosis (MS), brain atrophy measurements have emerged as an important biomarker reflecting neurodegeneration and disability progression. However, due to several potential confounders, investigation of brain atrophy in clinical routine and even in controlled clinical studies can be challenging. The aim of this study was to investigate the short-term dynamics of brain atrophy development after initiation of disease-modifying therapy (DMT) in a “real-world setting.” Methods In this retrospective study, we included MS patients starting DMT (natalizumab, fingolimod, dimethyl fumarate, or interferon-ß1a) or without DMT, availability of a baseline MRI, and two annual follow-up scans on the same MRI system. Two-timepoint percentage brain volume changes (PBVCs) were calculated. Results Fifty-five MS patients (12 patients starting DMT with natalizumab, 7 fingolimod, 14 dimethyl fumarate, 11 interferon-ß1a, and 11 patients without DMT) were included. We found the highest PBVCs in the first 12 months after initiation of natalizumab treatment. Furthermore, the PBVCs in our study were very much comparable to the results observed by other groups, as well as for fingolimod, dimethyl fumarate, and interferon-ß1a. Conclusion We found PBVCs that are comparable to the results of previous studies, suggesting that brain atrophy, assessed on 3D MRI data sets acquired on the same 3T MRI, provides a robust MS biomarker.
Online veröffentlicht: 25. Juli 2023
Gesehen am 18.07.2024